Microenvironment-responsive injectable hydrogel for neuro-vascularized bone regeneration - Wanshun Wang; Hu Chen; Jiacong Xiao; Dan Luo; Yonghui Hou; Jiheng Zhan; Yu Hou; Xing Li; Huili Yang; Shudong Chen; Dingkun Lin (Materials Today Bio)
Bone is a richly innervated and vascularized tissue, whereas nerve-vascular network reconstruction was often ignored in biomaterial design, resulting in delayed or incomplete bone healing. Inspired by the bone injury microenvironments, here we report a controllable drug delivery strategy using a pH and reactive oxygen species (ROS) dual-response injectable hydrogel. Based on the dynamic borate ester bond covalent crosslinking, nano-hydroxyapatite (HA) and curculigoside (CCG) are integrated into PVA/TSPBA (PT) to construct a responsive injectable hydrogel (PTHC), which scavenges excessive ROS from the injury microenvironment and responsively releases HA and CCG, providing favorable homeostasis and in situ sustained release drug delivery system for bone repair. Additionally, PTHC hydrogel can alleviate ROS-mediated intracellular oxidative and exhibit multiple biological activities of angiogenesis, neurogenesis, and osteogenesis. Furthermore, it reconstructs the microvascular network, accelerates sensory nerve repair, secretes neurotransmitters and bioactive factors, and improves neuro-vascularized bone regeneration. This multi-bioactive injectable hydrogel system offers a promising advance in therapeutic materials for bone repair.